Interrupted versus continuous suture for bronchial anastomosis in lung transplantation: does it matter?. (4th October 2022) - Gil Barturen, Mariana; Campo-Cañaveral de la Cruz, Jose Luis; Crowley Carrasco, Silvana; Romero Román, Alejandra; Hoyos Mejía, Lucas; Peyró, María; Díaz Nuevo, Gema; López García-Gallo, Cristina; Pérez Redondo, Marina; Royuela Vicente, Ana; Tanaka, Shin; Naranjo Gómez, Jose Manuel; et al.
Abstract: OBJECTIVES: Bronchial anastomotic complications remain a major concern in lung transplantation. We aim to compare 2 different techniques, continuous suture (CS) versus interrupted suture (IS) by analysing airway complications requiring intervention. METHODS: Lung transplantations between January 2015 and December 2020 were included. Airway complications requiring intervention were classified following the 2018 International Society for Heart and Lung Transplantation consensus and analysed comparing 3 groups of patients according to surgical technique: group A, both anastomosis performed with CS; group B, both with interrupted; and group C, IS for 1 side and CS for the contralateral side. RESULTS: A total of 461 anastomoses were performed in 245 patients. The incidence of airway complications requiring intervention was 5.7% [95% confidence interval (CI): 2.8–8.6] per patient (14/245) and 3.7% (95% CI: 2.0–5.4) per anastomosis (17/461). Complications that required intervention were present in 5 out of 164 (3.1%) anastomosis with interrupted technique, and in 12/240 (5%) with CS. No significant differences were found between techniques ( P = 0.184). No statistical differences were found among group A, B or C in terms of incidence of anastomotic complications, demographics, transplant outcomes or overall survival (log-rank P = 0.513). In a multivariable analysis, right laterality was significantly associated to complications requiring intervention (OR 3.7 [95% CI: 1.1–12.3], P = 0.030). Endoscopic treatment was successful in 12 patients (85.7%). Retransplantation was necessary in 2 patients. CONCLUSIONS: In summary, although it seems that anastomotic complications requiring intervention occur more frequently with CS, there are no statistical differences compared to IS. Endoscopic treatment offers good outcomes in most of the airway complications after lung transplantation. Abstract : Despite increasing experience in lung transplantation (LTx) and the improved general outcomes worldwide, there are still several matters subject to open discussion, one of which being the bronchial anastomosis technique.